Nasopharyngeal Acid Reflux and Eustachian Tube Dysfunction in Adults. (June 2014) - Brunworth, Joseph D.; Mahboubi, Hossein; Garg, Rohit; Johnson, Brandon; Brandon, Bryan; Djalilian, Hamid R.
Objective: This study aimed to evaluate the relationship between nasopharyngeal pH and Eustachian tube dysfunction (ETD) in adults. Study Design: Unmatched case-control study. Methods: Forty-one subjects, 20 adults with a diagnosis of ETD and 21 healthy adults as controls, were enrolled from an outpatient clinic. All subjects had a Dx–pH probe placed near the torus tubarius in the posterior nasopharynx for 24 hours. The pH values were recorded every 0.5 second. Decreases in pH were considered as reflux events if the pH dropped below 5.5. Results: The average nasopharyngeal pH value was 6.90 (range, 5.33-7.73) in the subjects with ETD and 7.07 (range, 5.99-7.94) in the controls. The difference between the 2 groups was not statistically significant ( P = .30). The ETD group, on average, had a higher number of nasopharyngeal reflux events (2.3 ± 1.6 vs 0.8 ± 1.2, respectively; P = .002) and higher reflux finding score (3.6 ± 2.7 vs 0.4 ± 1.4, respectively; P < .001) than the control group. Conclusion: By using a novel pH probe that allows detection of acidity in a nonliquid environment, a comparison of nasopharyngeal pH between control patients and those with ETD was performed. Eustachian tube dysfunction was more likely to be associated with a higher number of nasopharyngeal reflux events and higher reflux finding score. Nasopharyngeal reflux may have a role in the pathogenesis of ETD.